A study to determine the effectiveness of conjunctival autograft as an alternative to normal surgical procedures to reduce the recurrence of pterygium - Padala Venkateswara Prasad; Bhanumurthy Gangalapuram; Shyamprasad Bukkapatnam Ramachandra (Asian Journal of Medical Sciences, 2022)
Background: Pterygium is a chronic degenerative condition, in which a triangular fibrovascular growth of bulbar conjunctiva encroaches on the cornea. It is a cause of concern for both the patient due to its unsightly appearance and the surgeon due to its tendency to recur. Aims and Objectives: The present study was undertaken to determine the effectiveness of conjunctival autograft as an alternative to normal surgical procedures to reduce the recurrence of pterygium. Materials and Methods: A total of 30 patients with primary and recurrent pterygia who attended the ophthalmology, outpatient department were taken up for the study after obtaining informed consent. A standard surgical technique essentially similar to that described by Kenyon et al., was followed in all patients with a few minor modifications. All surgeries are performed using an operating microscope. Results: The majority of patients belonged to the 3rd and 4th decades. In our study of 30 cases, we had a recurrence rate of 3.0%. The results and outcome of pterygium surgery in our series stress the importance of conjunctival autograft as the procedure of choice for the surgical management of primary and recurrent pterygium in Indian eyes. The success of conjunctival autograft may be related to the significant learning curve and different surgical techniques for these procedures. Conclusion: Conjunctival autograft proves to be a simple safe and inexpensive technique with low recurrence rates for pterygium in young people. Although conjunctival autograft is a time-consuming procedure and has a significant learning curve, it is the procedure of choice for pterygium. Further detailed studies with a higher sample size are needed in this area.